Factors Influencing the Behavioural Intention to Use AI-Generated Images in Business - Maican, Catalin Ioan; Sumedrea, Silvia; Tecau, Alina; Nichifor, Eliza; Chitu, Ioana Bianca; Lixandroiu, Radu; Bratucu, Gabriel (IGI Global, 2023)
Motivated by the need to better understand the ongoing role of artificial intelligence in businesses and to shift the focus from a purely technological and algorithmic perspective to one that encompasses human-computer interaction, this article aims to investigate people's intention to use AI for generating images in a business context. The present study employed structural equation modelling to analyse how factors from UTAUT2 such as perceived customer value, effort expectancy, social influence, and facilitating conditions affect behavioural intention. The research introduces new moderators (creativity and English language proficiency), in the context of generative AI. Language proficiency and gender impact AI usage, while the impact of effort expectancy is more pronounced in cases of low creativity.